2017
DOI: 10.3389/fped.2017.00207
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curves for Laparoscopic Repair of Inguinal Hernia and Communicating Hydrocele in Children

Abstract: IntroductionWe analyzed the department and surgeon learning curves during implementation of the percutaneous internal ring suturing (PIRS) technique in our department.MethodsChildren proposed for inguinal hernia or communicating hydrocele repair were included (n = 607). After mentorship, all surgeons were free to propose open or PIRS repair. From gathered data, we assessed department and surgeon learning curves through cumulative experience focusing in perioperative complications, conversion, ipsilateral recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
2
24
0
1
Order By: Relevance
“…It is assumable that the latter two reasons tend to occur more frequently when the surgery is performed by inexperienced surgeons. The learning curve of the laparoscopic percutaneous extra-corporeal technique varies between 31 and 48 operations for paediatric surgical trainees and between 12 and 35 operations for surgeons (34)(35)(36). Since the extra-corporeal technique does not require intraperitoneal suturing, it is expected to have a lower learning curve than the intra-corporeal technique.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumable that the latter two reasons tend to occur more frequently when the surgery is performed by inexperienced surgeons. The learning curve of the laparoscopic percutaneous extra-corporeal technique varies between 31 and 48 operations for paediatric surgical trainees and between 12 and 35 operations for surgeons (34)(35)(36). Since the extra-corporeal technique does not require intraperitoneal suturing, it is expected to have a lower learning curve than the intra-corporeal technique.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of minimally invasive medicine and increasing development of various minimally invasive surgical instruments, the pediatric inguinal hernia surgery has gradually transitioned from the traditional open surgery through the groin to minimally invasive laparoscopic surgery and developed from the original three-port and two-port laparoscopy to the latest transumbilical single-port laparoscopic surgery [7][8][9]. Meanwhile, the closure method of hernial inner ring opening has developed from the initial intraperitoneal suture and ligation to the current laparoscopic percutaneous extraperitoneal closure (LPEC) [10][11][12][13]. Moreover, some scholars have also reported the use of various home-made surgical instruments for single-site laparoscopic herniorrhaphy to treat pediatric inguinal hernia, and favorable efficacy has been attained [14].…”
Section: Discussionmentioning
confidence: 99%
“…How to reduce the recurrence rate after single-port laparoscopic inguinal herniorrhaphy in children is a major problem in clinical practice at present, and the most common causes of recurrence include the learning curve factor, indefinite ligation, and ligature loosening [13,17]. Research shows that although there were individual differences, all trainees acquired the skill to perform LPEC adequately within ten months [18].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that about ninety percent of complications are avoided when the repair is performed during the first month of diagnosis. Plethora of surgeons have recommended hernia repair immediately after diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…The first laparoscopic repair of inguinal hernia repair was reported round the 1990s, [3], since then many techniques have been described which can be divided in to two major groups [2]; intra-corporeal technique that included dissection, ligation and division of the sac that resemble the true classic inguinal herniotomy [4,5]…”
Section: Introductionmentioning
confidence: 99%